On the applicability of electromagnetic monitoring of hydraulic fracturing - Gleb S. Grigorev; Mikhail V. Salishchev; Natalia P. Senchina (Записки Горного института, 2021)
The purpose of this work is to assess the possibilities of using electromagnetic monitoring to study the development of a fracture system generated by hydraulic fracturing (HF) with a specified position of the controlled source. The option with the source (a vertical electric dipole) located in the interval of the oil-bearing formation and ground-based measurements was chosen as the most promising monitoring plan. We have built a geoelectric model equivalent to the system of hydraulic fractures, divided into 11 zones corresponding to HF stages. For the selected model, mathematical simulation was performed by solving the direct problem considering the impact of the steel casing, the presence of which reduced the effect. Despite this fact, no strong distortion of electromagnetic field anomaly was observed above the HF zone. Analysis of the simulation results at different HF stages showed that as new hydraulic fractures appeared and were filled with electrically conductive proppant, the total effect increased. The data on electric field anomaly demonstrated maximum deviation from the background level of more than 2 %. Provided that the studied formation is characterized by sufficient electrical conductivity, its magnetic field also becomes informative.